2023
DOI: 10.3390/cryst13060976
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Polydopamine for Surface Modification and Enhancement of Energetic Materials: A Mini-Review

Abstract: Polydopamine (PDA), inspired by the adhesive mussel foot proteins, is widely applied in chemical, biological, medical, and material science due to its unique surface coating capability and abundant active sites. Energetic materials (EMs) play an essential role in both military and civilian fields as a chemical energy source. Recently, PDA was introduced into EMs for the modification of crystal phase stability and the interfacial bonding effect, and, as a result, to enhance the mechanical, thermal, and safety p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Inspired by the composition of adhesive proteins in mussels, Lee and co-workers 16,17 have shown that dopamine (DA) through the self-polymerization process can form thin, surface-adherent polydopamine films (PDA) 18,19 onto a wide range of inorganic and organic materials, including noble metals, oxides, polymers, semiconductors, and ceramics. 20–26…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the composition of adhesive proteins in mussels, Lee and co-workers 16,17 have shown that dopamine (DA) through the self-polymerization process can form thin, surface-adherent polydopamine films (PDA) 18,19 onto a wide range of inorganic and organic materials, including noble metals, oxides, polymers, semiconductors, and ceramics. 20–26…”
Section: Introductionmentioning
confidence: 99%